2023
DOI: 10.1002/ejp.2139
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of smoking cessation and resumption on back pain risk in later life

Abstract: BackgroundThis study aimed to assess the impacts of smoking cessation and resumption over 4 years on the risk of back pain at the 6‐year follow‐up among older adults in England.MethodsWe analysed 6467 men and women aged ≥50 years in the English Longitudinal Study of Aging. Self‐reported smoking status, assessed in waves 4 (2008–2009) and 6 (2012–2013), was used as exposure for the study, whereas self‐reported back pain of moderate or severe intensity, assessed in wave 7 (2014–2015), was used as the outcome. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Given the multi-perspective negative impacts of smoking on spinal health, we found that changes in smoking behavior, such as quitting smoking and not smoking, led to a decrease in BP risk, which is consistent with previous research [14,34], while lowering smoking volume and intensity resulted in a more significant BP risk reduction among current smokers. One potential explanation for this observation is the recovery process that occurs after prolonged nicotine consumption, in which the central nervous system undergoes a restorative phase, leading to a reduction in over-amplified pain perception following the discontinuation of nicotine exposure [35].…”
Section: Back Pain Incidence (95% Ci) P-valuesupporting
confidence: 91%
“…Given the multi-perspective negative impacts of smoking on spinal health, we found that changes in smoking behavior, such as quitting smoking and not smoking, led to a decrease in BP risk, which is consistent with previous research [14,34], while lowering smoking volume and intensity resulted in a more significant BP risk reduction among current smokers. One potential explanation for this observation is the recovery process that occurs after prolonged nicotine consumption, in which the central nervous system undergoes a restorative phase, leading to a reduction in over-amplified pain perception following the discontinuation of nicotine exposure [35].…”
Section: Back Pain Incidence (95% Ci) P-valuesupporting
confidence: 91%